Orbital Myiasis: Due to Invasion of Larvae of Flesh Fly (Wohlfahrtia magnifica) in a Child; Rare Presentation - R. P. Maurya; Deepak Mishra; Prashant Bhushan; V. P. Singh; M. K. Singh (Case Reports in Ophthalmological Medicine)
Wohlfahrtia magnifica larvae cause myiasis in mammals, mainly in sheep and rarely in human. In human it may infest the ear, eye, mouth or nose, damaging living tissues. We report a case of ocular myiasis in 1.5 years old child belonging to urban slum after history of minor injury on left upper lid due to fall from bed. The purpose of reporting this case is to highlight the ocular association of W. magnifica.